If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -45 = 2y Reorder the terms: -45 + 3x = 2y Solving -45 + 3x = 2y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '45' to each side of the equation. -45 + 45 + 3x = 45 + 2y Combine like terms: -45 + 45 = 0 0 + 3x = 45 + 2y 3x = 45 + 2y Divide each side by '3'. x = 15 + 0.6666666667y Simplifying x = 15 + 0.6666666667y
| -6(2x-1)=0 | | x^2-15=-7x+2 | | 23-5n=-7(n-3)-4 | | 0.1x+0.2y=-0.2 | | Log^4*16=2 | | 7x-(5x+4)=9x-25 | | 25=2u+3u | | 2(x+4)4=0 | | 7.4x-13.4=31 | | 8u-u=21 | | 128-4y+2y=100 | | (c-3)(2c)=2c(c-3)-c^2+4 | | 16x-14=-110 | | 18x+14=13x+4 | | 5x+40=15-50 | | x+11=7x+65 | | 3a-3+2a=200-3a+2a | | (2b-4)=7b+2 | | 5=4x(1+x) | | 7.35x+66.15=132.3 | | -x+1=28+2x | | 3-4x+8x-5x=3x+12-15x+7 | | 4x-8.6=48.1-5x | | 8+12+(-9)-(-6)= | | 4x-7=29-2x | | 56-7x=-48+6x | | 5(x+1)=6-2(5x-7) | | x^2+9x-12=6+2x | | 8n+3=9 | | 18=13x+4x | | 0.6(w-12)=0.2w | | -8b-[5b(7b-9b)]-[-3+(20b+3)]=0 |